Pipe surface inspection by Industrial machine vision - S. Subramanian, N. Raghothaman* (Recent Research in Science and Technology, 2010)
Metallurgy Industry which mainly transforms the steel or its derivative products into products with either better surface properties or into different shape products involves some processing tools which can often generate flaws within the process. The primary goal of this prototype is to provide a view of the whole surface of the pipe to the operator when the surface of the pipe is completely machined. Various lighting systems where tested so as to reveal the maximum number of defects such as tool marks, scratches, etc. The pipe surface being not smooth (rough), we found that a homogenous lighting (diffused) of the scene enabled a clear inspection of the tube surface and reveal most of the defects. We have taken nickel pipes which are used for oil prospecting and deep earth applications and using our optics along with machine vision camera we devised suitable software so that the inspection of the pipe surface is carried out on tool – inspect – tool basis. Since the tool contact area on the pipe surface is one square milli meter we divide the image of the pipe surface into several templates and analyze for flaws such as micro dints, micro lamination or micro fissure. The difficulties in real time image acquisition and analysis are thoroughly studied and overcome. The software has all options for image enhancement, analysis, measurement and also statistical process control options.